Escaping low-earnings in Germany - do employer characteristics make a difference? - Anja Heinze; Nicole Gürtzgen (Verein für Socialpolitik, 2010)
This paper studies the importance of employer-specific determinants in escaping low earnings in Germany. To address the initial conditions problem and the endogeneity of employer retention, we model (intra-firm) low-pay transitions using a multivariate Probit model that accounts for selection into low-wage employment and non-random employer drop-out. Using data from the LIAB Linked Employer-Employee panel, our results for the service sector indicate that for male workers the probability of escaping low-pay increases with employer size. This contrasts with female workers, who rather benefit from collective bargaining coverage and local works councils. These findings are consistent with internal labour markets being an important ingredient of male within-firm wage growth, whereas the removal of asymmetric information appears to be more relevant in explaining female workers' wage transitions.
Keywords: C23; J31; J51; 330; Wage Mobility; Trivariate Probit; Linked Employer-Employee Data